Concepts in the design and engineering of single- molecule electronic devices. Issue 2 (2019) - Xin, Na; Guan, Jianxin; , Chenguang Zhou; Nitzan, Abraham; Chen, Xinjiani; Gu, Chunhui; Stoddart, J. Fraser
No abstract available